1998
DOI: 10.1097/00041433-199812000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and coronary artery disease

Abstract: Data on the protective role of antioxidants in models of atherosclerosis are only partially confirmed in man. Observational and epidemiological data, as well as randomized trials, provide no clear cut indications, because of positive and disappointing results on the use of antioxidants in cardiovascular protection. Despite the lack of a general consensus, recent data reinforce the concept that the regular intake of antioxidants present in food limits the progression of atherosclerosis. When it is possible to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 64 publications
0
13
0
2
Order By: Relevance
“…So far, only a few small, prospective, epidemiological studies that evaluate the association between surrogate markers of oxidative stress and CVD are available in CKD patients (43,(125)(126)(127). This is in contrast to the larger number of prospective epidemiologic studies in the general population, which links low intake of dietary antioxidants to cardiovascular risk (128).…”
Section: Oxidative Stress-an Intricate But Promising Area In Ckdmentioning
confidence: 99%
“…So far, only a few small, prospective, epidemiological studies that evaluate the association between surrogate markers of oxidative stress and CVD are available in CKD patients (43,(125)(126)(127). This is in contrast to the larger number of prospective epidemiologic studies in the general population, which links low intake of dietary antioxidants to cardiovascular risk (128).…”
Section: Oxidative Stress-an Intricate But Promising Area In Ckdmentioning
confidence: 99%
“…Antioxidants have been shown to slow down the atherosclerotic process, but their mechanisms of action are only poorly understood (Olsson & Yuan, 1996;Diaz, et al, 1997;Faggiotto et al, 1998). Antioxidants are able to modulate LDL oxidation (Heinecke, 1998), and also act at the cellular level by modulating the activity of various intracellular signalling pathways and inhibiting the pathogenic e ects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, various observational studies have suggested that the intake of antioxidant vitamins (vitamins C, E, etc.) is effective for the prevention of atherosclerotic diseases 28) . However, as many of the large-scale clinical studies performed recently presented negative views on a significant preventive effect of high-dose administration of vitamins C and E on atherosclerotic diseases, there are no solid grounds for recommending the intake of antioxidant vitamins in addition to regular meals for the prevention of the progression of atherosclerosis [29][30][31] .…”
Section: Smoking Cessationmentioning
confidence: 99%